Modeling the process of decay heat imitation in the corium at the «Lava-B» facility - Toleubekov, K.O.; Baklanov, V.V.; Akayev, A.S.; Bekmuldin, M.K. (Recent Contributions to Physics, 2022)
It is known that corium is produced during the development of a severe accident at a nuclear power plant from a melt of core materials [1]. An important feature of the corium formed in an operating reactor is the presence of decay heat. Thus, it is especially important to take into account the presence of decay heat when conducting calculations and physical experiments, since it influences significantly on the nature of interaction between corium melt and structure materials of a reactor facility. For that reason, methods of decay heat simulation are subject to quite serious requirements to the depth and intensity of energy release in the corium when conducting different experiments. This article considers induction and plasmatron heating technologies as methods to simulate decay heat in corium at the Lava-B facility. Characteristics of the selected methods of heating the corium prototype was analyzed by means of computer modeling. As a result of the work, parameters of melt heating using each of the considered methods were determined, and they were also cmpared. The used thermophysical models were created in the widely known ANSYS software based on the experimental section, which was used in one of the experiments at the Lava-B facility [2]. The main parameters of the corium-heater system were obtained by computer modeling for each of the considered methods and limits of their applicability for simulation of decay heat were determined when conducting the experiments at the facility.